The Portrait of Women in Election Campaign Advertisements - Kusnadi, Hajidah Fildzahun Nadhilah; Pradana, Bagus Cahyo Shah Adhi; Suhadianto, Suhadianto; Muchtar, Andi Reinsky (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Women are increasingly participating actively in the political sphere; However, their representation in political campaign media often remains entrenched in patriarchal discourse. This study aims to analyze the visual and textual constructions in two political campaign posters of female legislative candidates from the Indonesian Solidarity Party (PSI), which incorporate the terms in branding with “Mamah Muda” and “Mamah Semok” as part of their personal branding. Employing the Multimodal Critical Discourse Analysis approach (Kress & van Leeuwen), this research explores how the meaning of female body representation is constructed through the combination of imagery, text, color, and symbols in campaign posters. The findings reveal that the representation of female candidates continues to be framed through maternal yet sensual imagery and patriarchal aesthetics that emphasize visual appeal. Such portrayals reinforce softened femininity norms and internalize power relations that position women as visual objects. This study concludes that political campaigns in Indonesia have not fully escaped from gender-biased narratives, and that the political arena remains a non-neutral space in terms of gender.